-4x-3(-7x-16)=-139

Simple and best practice solution for -4x-3(-7x-16)=-139 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-3(-7x-16)=-139 equation:


Simplifying
-4x + -3(-7x + -16) = -139

Reorder the terms:
-4x + -3(-16 + -7x) = -139
-4x + (-16 * -3 + -7x * -3) = -139
-4x + (48 + 21x) = -139

Reorder the terms:
48 + -4x + 21x = -139

Combine like terms: -4x + 21x = 17x
48 + 17x = -139

Solving
48 + 17x = -139

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-48' to each side of the equation.
48 + -48 + 17x = -139 + -48

Combine like terms: 48 + -48 = 0
0 + 17x = -139 + -48
17x = -139 + -48

Combine like terms: -139 + -48 = -187
17x = -187

Divide each side by '17'.
x = -11

Simplifying
x = -11

See similar equations:

| 2h=10-7a | | 2(5x-5)-5(3x+10)=0 | | -17+3n=7(n-2) | | k+k+k= | | x+4=2(0.4x+1.3) | | -30=4-8x | | 1.5b-1=0.125(12b-8) | | v=0.7142857143+0.4285714286d | | -5y=-15-x | | (10*4)*6= | | 7v=3d+5 | | 2z=-4z+18 | | 3y-4=-1 | | 16r-23=6r-13 | | 3x-15+2x=9x-32 | | 120=7x+x | | 6x-6(-x+2)=48 | | 5x-35=x+17 | | x^2-60=11x | | 16x-14=14x+20 | | 4x-2=86 | | 3(x-5)=2x+11 | | 3d=7v+5 | | c=1.20+0.95(1-1) | | (4y)2y= | | 5y+6=3y+6 | | 4a+10=-a+15 | | 2x+2(-7x-8)=80 | | 0.75c-0.11=0.23(c-5) | | 6(y-1)=2y-18 | | 14=2x+26 | | -x-1=y |

Equations solver categories